2021
DOI: 10.1063/5.0065193
|View full text |Cite
|
Sign up to set email alerts
|

Precise prediction of the drag reduction efficiency of polymer in turbulent flow considering diameter effect

Abstract: One important issue for drag reduction of turbulent flow with polymers is the pipe diameter effect. Although this scale-up effect has been extensively investigated, there are still debates. For instance, when using the traditional scaling law to predict the friction factor in pipe flow of wide pipe diameters, the relative errors between experimental data and predicted values can be up to 1000%. This paper develops a new method to predict the friction factor in pipe flow applicable to a wide range of pipe diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Hoyt et al , proposed one model for the prediction of friction factor: R e f / d was a constant when polymer type, molecular weight, and polymer concentration were the same. In our previous work, , we extract data from previous research and rearrange them in a Prandtl–von Karman coordinate with log 10 ( Re f ) vs 1 / f . The results showed that all data can be fitted in a straight line, which follows the format in eq .…”
Section: Resultsmentioning
confidence: 99%
“…Hoyt et al , proposed one model for the prediction of friction factor: R e f / d was a constant when polymer type, molecular weight, and polymer concentration were the same. In our previous work, , we extract data from previous research and rearrange them in a Prandtl–von Karman coordinate with log 10 ( Re f ) vs 1 / f . The results showed that all data can be fitted in a straight line, which follows the format in eq .…”
Section: Resultsmentioning
confidence: 99%